Disclosure Regulations and Political Accountability Does Government Capital Ownership Influence Companies Performance Evidence from ASEAN Countries - Dini Maulana Lestari; Slamet Haryono; Reni Furwanti (Fakultas Ekonomi dan Bisnis Islam, Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri Purwokerto, 2021)
This research aims to discuss those four aspect toward companies’ performance. Government capital ownership is another crucial aspect which able to consider by companies for increase their performance. This is because the higher perentage government capital have, the biggest power they able to control the companies, and it is a good condition because they able to reduce agency’s issues between management and shareholders which absolutely brings positive influence on companies’ performance. Nevertheless, it still lack of studies which combined mandatory, voluntary disclosrues, political accountability and government capital ownership for measuring companies performance. The result come out that although government capital ownership brings no significant effect to boost companies’ performance, it is able to moderating the variable of mandatory, voluntary disclosures and political accountability have significant positive effect to increase companies’ performance.